Developing and testing a community based, online vs. face-to-face peer led intervention to improve mental well-being in Cambodian adults with physical disabilities - Best, Paul; Maddock, Alan; Ean, Nil; Montgomery, Lorna; Armour, Cherie; Mulholland, Ciaran; Blair, Carolyn (Frontiers in Digital Health, 2024)
BackgroundDespite growing international attention, there remains an urgent need to develop mental health services within low and middle income countries. The Khmer Rouge period in Cambodia saw the destruction of all health services infrastructure in the 1970s. Consequently, Cambodia has struggled to rebuild both its economy and healthcare system, with the number of qualified mental health clinicians remaining disproportionately low. Resultantly, there is a pressing need to develop low-cost community based alternatives of mental healthcare.MethodsUsing a mixed methods design, researchers developed an 8-week peer-led intervention, known as a Friendship Group, for adults with physical disabilities using both face-to-face and online delivery methods. The Wilcoxon Signed-Rank test was used to assess changes in pre-post survey scores and qualitative data was collected in form of five focus groups post intervention.Results41 participants were allocated across four Friendship groups – two were online and two face-to-face. Attrition rate was 22% post-intervention (n = 32). ITT analyses showed a statistically significant decrease in psychological distress scores [Z = −3.808, p < .001] from pre [Mdn = 20, IQR = 16.5–25.5] to post [Mdn = 16, IQR = 14–18.5] intervention. A Wilcoxon signed-ranks test also showed a statistically significant decrease in PTSD scores [Z = −2.239, p < .025] from pre [Mdn = 4, IQR = 3–5] to post [Mdn = 3, IQR = 2.75–4] intervention. There was also a statistically significant decrease in worry scores [Z = −3.904, p < .001] from pre [Mdn = 5, IQR = 3.5–6.5] to post [Mdn = 3, IQR = 3–4] intervention. There were no significant group differences between the face to face and online groups. A number of interconnected themes emerged from focus group data (n = 5), these included the mental health benefits of Friendship Groups as conceptualised through knowledge acquisition, skill development and peer support.ConclusionsThe Friendship group intervention delivered in both online and face-to-face formats appears feasible and acceptable within the Cambodian context. Initial data revealed positive findings in terms of reduction in psychological distress, worry and PTSD symptoms as well increased feeling as calm.